2019
DOI: 10.1111/apa.15111
|View full text |Cite
|
Sign up to set email alerts
|

Parental understanding of relapsing idiopathic nephrotic syndrome—Where are the knowledge gaps?

Abstract: AimTo assess parental understanding of idiopathic nephrotic syndrome (INS) and its management, to enable targeted education in areas of deficit.MethodsFamilies of children with at least one relapse of INS were interviewed, following a template covering key domains of (a) disease understanding, (b) management of INS and (c) access to information. Common trends and responses were identified and notable observations recorded.ResultsTwenty‐one parents were interviewed. The mean duration of INS was 4.4 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Also, we detected lack of discussion about access to healthy food and whether these families could afford the cost of suitable foods or not. Similarly, Lo Cao et al 18 reported 57% of their Australian cohort were not on appropriate controlled diet during remission.…”
Section: Discussionmentioning
confidence: 93%
“…Also, we detected lack of discussion about access to healthy food and whether these families could afford the cost of suitable foods or not. Similarly, Lo Cao et al 18 reported 57% of their Australian cohort were not on appropriate controlled diet during remission.…”
Section: Discussionmentioning
confidence: 93%
“…13 Meanwhile, parents are required to deal with frequent follow-up visits to the hospital, school challenges, and dietary restrictions. 14,15 These responsibilities are challenging as well as stressful for parental caregivers.…”
Section: Introductionmentioning
confidence: 99%